Individualized management of biliary tract injuries in pediatric patients: Lessons from a pediatric surgical center - Diana Lizbeth Escobedo Duarte; Edgar Fernando Oliver García; Oscar Ferrer Delgado Herrera; Pierre Jean Aurelus; Sofia Brenes Guzmán; Juan Carlos Nuñez Enríquez; Cesar Eduardo Vallín Orozco (Elsevier, 2024)
The biliary pathology, once uncommon in children has shown an increasing prevalence in this age group. This trend underscores the importance of having highly skilled surgeons with expertise in biliary tree management to avoid biliary duct injury (BDI). Methods: A retrospective study analyzed 21 patients with biliary tract injuries from 2010 to 2022. It provides a descriptive analysis, raising concerns about its clinical value and emphasizing the need to understand biliary anatomy to prevent such injuries. Results: Patients ranged from 0 to 17 years, with 57.1 % females and 42.9 % males. The most common primary diagnoses were hepatic tumors (33.3 %), chronic calculous cholecystitis, and choledochal cysts (23.8 % each). Surgical procedures included hepatectomy (33.2 %), choledochal cyst resection (23.8 %), and laparoscopic cholecystectomy (28.6 %). Conservative management was chosen in 28.1 % of cases, while surgery was performed in 71.4 %. Complications included bilioma (23.8 %), biliary fistula, and cholangitis (19 % each). Twelve patients underwent a second intervention, six requiring a third intervention, with hepaticojejunostomy being the most common (57.1 %). One patient received a liver transplant from a related living donor. The mortality rate was 9.5 %, with a median hospital stay of 35 days. Concussion: BDI in pediatric patients poses challenges and is on the rise. Recognition of biliary anatomy is crucial to prevent injury. Clinical presentation includes fever, pain, jaundice, and cholestasis. Imaging studies aid early diagnosis. Specialized centers and precise classification are essential for optimal management. Less invasive options maybe suitable for mild cases, while hepaticojejunostomy remains standard for severe injuries. Further research is needed to refine management protocols and reduce morbidity and mortality in these complex cases.